2016
DOI: 10.1073/pnas.1603127113
|View full text |Cite
|
Sign up to set email alerts
|

IGF-1 degradation by mouse mast cell protease 4 promotes cell death and adverse cardiac remodeling days after a myocardial infarction

Abstract: Heart disease is a leading cause of death in adults. Here, we show that a few days after coronary artery ligation and reperfusion, the ischemia-injured heart elaborates the cardioprotective polypeptide, insulin-like growth factor-1 (IGF-1), which activates IGF-1 receptor prosurvival signaling and improves cardiac left ventricular systolic function. However, this signaling is antagonized by the chymase, mouse mast cell protease 4 (MMCP-4), which degrades IGF-1. We found that deletion of the gene encoding MMCP-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 34 publications
5
41
2
Order By: Relevance
“…Locally, we found an increase of MCPT4 in kidney capsule extracts, while FcεRIb expressing MCs remain stable. Likely, kidney capsule MCs synthesize new chymase following local degranulation after renal IRI, as already reported after heart infarction, 52 may also enter local inflammatory sites from systemic sources.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Locally, we found an increase of MCPT4 in kidney capsule extracts, while FcεRIb expressing MCs remain stable. Likely, kidney capsule MCs synthesize new chymase following local degranulation after renal IRI, as already reported after heart infarction, 52 may also enter local inflammatory sites from systemic sources.…”
Section: Discussionsupporting
confidence: 63%
“…This protective function may be operative only during the acute phase, as MCPT4 also has detrimental effects in IRI during the later remodeling phase, as has been found in ischemic heart disease. 52 In fact, previous analyses of MCs and their mediators in kidney disease have revealed a complex picture. Some studies on MCs and MCPT4 showed that they aggravate glomerulonephritis, 26,53 whereas others reported diseaseprotective effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, fibronectin and angiotensin I seem to be common targets for the chymases of many mammals (37). Recently, it also was shown that mMCP-4 degrades IGF-1, leading to adverse effects in cardiac remodeling after infarction (25). In this study, we showed that HC and hCG cleave human IGF-1 (Fig.…”
Section: Discussionmentioning
confidence: 50%
“…Following our analysis of the above 50 cytokines and chemokines, an article was published showing the cleavage of insulin-like growth factor 1 (IGF-1) by the mouse chymase mMCP-4 (25). Therefore, we decided to examine the potential cleavage of this growth factor by HC and hCG.…”
Section: The Journal Of Immunologymentioning
confidence: 99%